Influence of sowing dates and nitrogen levels on the performance of summer-irrigated sorghum in the western agroclimatic zone of Tamil Nadu - Ammaiyappan, A; Geethalakshmi, V; Bhuvaneswari, K; Kalarani, M K; Thavaprakaash, N; Prahadeeswaran, M (Plant Science Today, 2025)
Sorghum is an important Nutri-cereal and stable food crop for majority of the populations in the semi-arid tropical regions. Climate change is predicted to have a detrimental impact on growth and the productivity of sorghum. Optimising the sowing windows and nitrogen levels are the major agronomic management practices which determine the better productivity of the crop. The field experiment was conducted in split plot design with three levels of replications. The main plots consist of five dates of sowing viz., D1-First fortnight of April, D2-Second fortnight of April, D3-First fortnight of May, D4-Second fortnight of May and D5-First fortnight of June. The sub plots include three different levels of nitrogen viz., N1-75 % RDN, N2-100 % RDN and N3-125 % RDN. The sorghum crop variety K 12 was used in this experiment and it was raised fully under summer irrigated conditions during 2023. The results indicated that sorghum sown on second fortnight of May (D4) recorded significantly higher the grain yield (4230.3 kg ha-1) and the yield increases were 15.9 % compared to first fortnight of April (D1-3649.5 kg ha-1). Regarding varied nitrogen levels125 % RDN (N3) registered highest grain yield (4063.6 kg ha-1) which increase of 5.8 % compared to the 100 % RDN (N2) (3839.5 kg ha-1). Further the delayed sowing of sorghum combined with increased nitrogen level give the highest gross return (Rs. 134424 ha-1), net return (Rs. 90100 ha-1) and B:C ratio (3.03) under summer irrigated condition.